MOTIVASI, KOMITMENT, KEPUASAN KERJA, KEINGINAN BERPINDAH KERJA SARJANA AKUNTANSI DI BENGKULU - Eriza, Tiara; saiful, saiful; Halimatusyadiah, Halimatusyadiah (JURNAL FAIRNESS, 2020)
The purpose of this research is to know the work motivation, commitment professional and work satisfaction on turnover intention of worker Accounting Graduate Worker in Bengkulu City. The population of this study are 123 peoples. The sample of this study was taken by census method. Data analysis in this research use descriptive statistic and multiple regression analysis. The results showed that: (1) the work motivation has a negative influence on turnover intention of worker Accounting Graduate Worker in Bengkulu City. It’s mean is if the motivation more increase, the turnover intention will be decrease; (2) the professional commitment has a negative influence on turnover intention of worker Accounting Graduate Worker in Bengkulu City. It’s mean is if the professional commitment more increase, the turnover intention will be decrease; and (3) the work satisfaction has a negative influence on turnover intention of worker Accounting Graduate Worker in Bengkulu City. It’s mean is if the work satisfaction more increase, the turnover intention will be decrease.